2020
DOI: 10.1016/j.ajp.2020.102188
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychiatric aspects of COVID-19 pandemic: A selective review

Abstract: Corona virus disease (COVID-19) has been declared as a controllable pandemic by the World Health Organization (WHO). COVID-19 though is a predominantly respiratory illness; it can also affect brain and other organs like kidneys, heart and liver. Neuropsychiatric manifestations are common during viral pandemics but are not effectively addressed. Fever and cough are common symptoms only in infected individuals but headache and sleep disturbances are common even in uninfected general public. In this selective rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0
12

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(93 citation statements)
references
References 61 publications
(72 reference statements)
2
79
0
12
Order By: Relevance
“…It is also seen that the involvement of SARS-CoV-2 with neurological aspects can affect different levels of the Central and Peripheral Nervous System, in addition to causing skeletal-muscular injury, representing 36.4% of the cases considered, including impairment of consciousness, ataxia, acute cerebrovascular disease, seizure and neuropathic pain, for example ( Bilbul et al, 2020 ). In an epidemiologically deeper approach, Dinakaran et al (2020) reinforces a percentage value close to the one reported by Bilbul et al (2020) regarding the neurological complaints of COVID-19 patients: 36%.…”
Section: Disorders and Epidemiological Profilessupporting
confidence: 77%
See 2 more Smart Citations
“…It is also seen that the involvement of SARS-CoV-2 with neurological aspects can affect different levels of the Central and Peripheral Nervous System, in addition to causing skeletal-muscular injury, representing 36.4% of the cases considered, including impairment of consciousness, ataxia, acute cerebrovascular disease, seizure and neuropathic pain, for example ( Bilbul et al, 2020 ). In an epidemiologically deeper approach, Dinakaran et al (2020) reinforces a percentage value close to the one reported by Bilbul et al (2020) regarding the neurological complaints of COVID-19 patients: 36%.…”
Section: Disorders and Epidemiological Profilessupporting
confidence: 77%
“…The COVID-19 takes, thereby, a pandemic feature, whose landmark is its effects on the respiratory system and its more serious manifestation: the Severe Acute Respiratory Syndrome ( Troyer et al, 2020 .). Due to the ability to generate multiple infections to systemic organs ( Jasti et al, 2020 ), the referred virus can cause damage to the kidneys, heart, liver and brain, for example ( Dinakaran et al, 2020 ). From a neurological perspective, individuals affected by the virus have reported headache, dizziness, hypogeusia and hyposmia during the course of the disease, with intensive care patients being more likely to complain of dizziness ( Zhou et al, 2020 ).…”
Section: Disorders and Epidemiological Profilesmentioning
confidence: 99%
See 1 more Smart Citation
“…Manifestations such as insomnia, anxiety, post-traumatic stress symptoms (PTSD), psychosis and mood disorders have been described in several reports (see Table 1; Dinakaran et al, 2020;Liguori et al, 2020;Nalleballe et al, 2020;Rogers et al, 2020;Romero-Sanchez et al, 2020;Vindegaard and Benros, 2020). A study that retrieved data from a global health collaborative platform that included medical records of 40,469 COVID-19 positive cases, mostly from the United States (US) (76%), found that 22.5% had neurological and/or psychiatric manifestations, being anxiety and related disorders the most prevalent (4.6%) (Nalleballe et al, 2020).…”
Section: Neuropsychiatric Manifestations Of Covid-19mentioning
confidence: 99%
“…A more realistic approach of study from the participants of the rst infection-affected area of hospitals in Wuhan showed more convincing metal-health states. Of all participants of health care workers especially nurses, women reported health and mental burden and those were undergone diagnosis management and treatment [34,35]. The present situation has affected different frontiers of lives and induced many psychiatric conditions in large number of individuals.…”
Section: Discussionmentioning
confidence: 99%